Peran Kepemimpinan Futuristik Terhadap Trasnformasi Perguruan Tinggi Institut Agama Islam Darussalam Blokagung Banyuwangi - Ikhsan Huzali; Moh. Fathul Ikhsan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Leaders are simply defined as someone who can move. This definition is increasingly complex in meaning when the leader is considered the top leader in higher education because one of the influences on the transformation of higher education is futuristic leadership, especially visionary leaders who have foresight for the development and improvement of campus quality to be competitive at the global level. This is where relationships, connections, and continuous improvement are needed, driven by higher education leaders who involve all stakeholders.The aims of this research are: 1) To describe the futuristic leadership of IAIDA Blokagung Banyuwangi; 2) Describe the transformation of IAIDA Blokagung Banyuwangi; 3) The influence of futuristic leaders on the transformation of IAIDA Blokagung Banyuwangi. This research approach is quantitative research with a descriptive research type. The data collection methods used in this study were interviews, questionnaires, observation, and documentation testing in research uses data validity tests using the product moment formula, fota reliability tests using the CornbaCronbach formula, for normality tests using the Kolmogorov-Smirnov formula. In data analysis using simple linear regression analysis. After conducting data analysis, it was found that: 1) the futuristic leadership implemented at IAIDA Blokagung was relatively good; 2) The institutional transformation of IAIDA Blokagung as a large pesantren-based campus in Banyuwangi district is also quite good by its efforts to periodically change its form; 3) The influence of futuristic leadership on the transformation of the IAIDA Blokagung Banyuwangi tertiary institution is 21%, while the other 79% is influenced by other factors outside of futuristic leadership. This shows that futuristic leadership is in a low category in influencing the transformation (change in shape) of IAIDA Blokagung Banyuwangi as a pesantren-based campus.